Institutional Tools of Innovative Modernization of Russian Megapolis Financial Market - S. A. Roshchektaev; A. N. Pogrebenko (Vestnik MGIMO-Universiteta, 2012)
The article is devoted to the justification of a new group of institutional instruments of innovative modernization of the financial market of the modern Russian megapolis – integrated network of development institutions. It is shown that these institutions are focused on the integration of the economic space of the megapolis and the rational structuring of the financial market.